“A source of empowerment and well-being”: Experiences of a dance and yoga intervention for young girls with functional abdominal pain disorders - Högström, Sofie; Eriksson, Mats; Mörelius, Evalotte; Duberg, Anna (Frontiers in Pediatrics, 2023)
Functional abdominal pain disorders are common among children and adolescents worldwide and effective treatments are needed to alleviate suffering for these children and their families. This study aimed to explore the experience of participating in a combined dance and yoga intervention from the perspectives of girls aged 9–13 years with functional abdominal pain disorders. A randomized controlled trial called Just in TIME (Try, Identify, Move and Enjoy) recruited 121 girls aged 9–13 years with functional abdominal pain disorders. The eight-month intervention combined dance and yoga twice a week, focusing on enjoyment, socialization and playful creativity in an undemanding and non-judgemental environment. The intervention group comprised 64 girls, of whom 25 were purposefully selected for this qualitative interview study. Semi-structured interviews were conducted and analysed using qualitative content analysis with an inductive approach. The girls’ experiences of the Just in TIME intervention can be described as “A source of empowerment and well-being which facilitated personal growth and new ways of engaging in life”. The main category was derived from six generic categories: “A sense of belonging”, “Joy and emotional expression through movement”, “Relief from pain”, “More self-confident”, “More active in daily life” and “A sense of calm.” In conclusion, regular participation in an eight-month intervention with combined dance and yoga in a supportive and non-judgemental atmosphere can ease pain and strengthen inner resources, resulting in empowerment, well-being and a more active life for girls with functional abdominal pain disorders. Trial registration: The Just in TIME study is available online at clinicaltrials.gov, ID: NCT02920268. Keywords: Dance, Experiences, Functional abdominal pain disorders, Intervention, Yoga